Factors contributing to the variation in the volatile composition of chocolate: Botanical and geographical origins of the cocoa beans, and brand-related formulation and processing. (June 2016) - Acierno, Valentina; Yener, Sine; Alewijn, Martin; Biasioli, Franco; van Ruth, Saskia
Abstract: The intrinsic characteristics of chocolate and the complex technological process complicate the assessment of the typical features of this product and the verification of its authenticity. In this study, the influence of the botanical and geographical origin of the cocoa beans, as well as the impact of brand-related processing on the volatile organic compound (VOC) composition of the resulting chocolates was examined. A total of ninety dark chocolates available on the Dutch market were analysed using Proton-Transfer-Reaction-Mass Spectrometry (PTR-MS). The VOC profiles generated by PTR-MS (136 masses per sample) were used as fingerprints and investigated using chemometric tools to elucidate information on production factors of cocoa and subsequent processing, in the finished product. Principal component analysis (PCA) showed some clustering of the chocolates according to the botanical and geographical origins of beans as well as according to the brand. Partial least square discriminant analysis (PLS-DA) further discriminated the samples according to the three classes (botanical origin, geographical origin, brand) and the models with the best classification results were used to investigate the relevant masses for each class. PCA clustering and PLS-DA classification highlighted that chocolate profiles are strongly affected by the processing applied by the different brands. However, reflection of the botanical and geographical origins of the beans was also mirrored in the VOC composition of the chocolates. PTR-Time of Flight-MS (PTR-ToF-MS) was used to tentatively identify the VOCs of the chocolates. These measurements allowed the identification of 36 spectrometric peaks which relate to the main classes of chocolate odorant compounds, in particular, aldehydes and pyrazines, products of Maillard reactions. Several compounds already present in unroasted beans were tentatively identified in the chocolates as well, such as, acetic acid, methylpropanoic acid, 2- and 3-methylbutanoic acid, 2-phenylethanol, and tetramethylpyrazine. The results of this study emphasize the impact of the brand-related formulation and processing on VOC profiles of dark chocolates. However, using chemometrics, VOC reflection of the botanical origin and geographical origin of the beans in the chocolates was revealed, which may be useful for a future cocoa/chocolate traceability. Graphical abstract: Highlights: Chocolate VOCs profiles are affected by brand-related processing. The influence of cocoa beans botanical and geographical origin could be detected. Chemometric tools discriminated chocolates and elucidated relevant VOCs. 36 spectrometric peaks related to beans and chocolate were tentatively identified. PTR-MS was shown to be useful in finding the link of raw material-–finished products.